Partial characterization and utilization of low-methoxyl pectin extracted from bell apple (Syzygium samarangense) in ice cream - Del Rosario, Eufemia Anne Salazar
Low-methoxyl pectin (LMP) is a well known gelling agent present in all plants. Contrary to the high-methoxyl pectin (HMP) used in jams and jellies. This study explored other potential sources of LMP, specifically bell apple (Syzygium samarangense), locally known as tambis.